2020
DOI: 10.3390/vaccines8010131
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Dose-Response to Adenovirus-Vectored Vaccines in Animals and Humans: A Systematic Review of Dose-Response Studies of Replication Incompetent Adenoviral Vaccine Vectors when Given via an Intramuscular or Subcutaneous Route

Abstract: Optimal vaccine dosing is important to ensure the greatest protection and safety. Analysis of dose-response data, from previous studies, may inform future studies to determine the optimal dose. Implementing more quantitative modelling approaches in vaccine dose finding have been recently suggested to accelerate vaccine development. Adenoviral vectored vaccines are in advanced stage of development for a variety of prophylactic and therapeutic indications, however dose-response has not yet been systematically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The dose of the viral vectors ChAdOx1 (10 9 UI/sheep) and MVA (10 8 PFU/sheep) used in our immunization strategy have been previously assessed in other sheep immunization assays and have been shown to be safe and efficient against RVFV [ 61 , 65 ]. These doses are below those used in human studies where even doses of 10 11 viral particles have been used for vaccines based on ChAdOx1 [ 66 ]. The augmented antigenic load has been suggested to affect qualitative aspects of CD8+ T-cell memory/effector responses [ 67 , 68 ] and, despite our results indicate that sheep immunized with ChAdOx1/MVA-NS1 were protected against BTV-4M infection, it would be interesting to analyze whether higher doses of vaccine are still safe for ruminants and completely reduce viremia after BTV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of the viral vectors ChAdOx1 (10 9 UI/sheep) and MVA (10 8 PFU/sheep) used in our immunization strategy have been previously assessed in other sheep immunization assays and have been shown to be safe and efficient against RVFV [ 61 , 65 ]. These doses are below those used in human studies where even doses of 10 11 viral particles have been used for vaccines based on ChAdOx1 [ 66 ]. The augmented antigenic load has been suggested to affect qualitative aspects of CD8+ T-cell memory/effector responses [ 67 , 68 ] and, despite our results indicate that sheep immunized with ChAdOx1/MVA-NS1 were protected against BTV-4M infection, it would be interesting to analyze whether higher doses of vaccine are still safe for ruminants and completely reduce viremia after BTV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it has been shown that higher doses trigger distinct, and sometimes more robust, activation of innate and adaptive immune pathways [25][26][27][28]. From an applied perspective, a better understanding of the immunogenic dose-response relationship is pertinent for optimising vaccine dosing to ensure improved safety and efficacy [21,[29][30][31]. However, because the functional output of immune activities (e.g., the rate of immune-mediated iRBC clearance) is Exchange Award).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus vectors are known to induce strong humoral, mucosal, and cellular immune responses to the encoded antigens. Based on data generated in numerous clinical protocols, adenovirus vectors are considered very effective vectored vaccines [ 43 , 44 ] and their mass production has been previously documented in an important number of studies [ 20 , 45 , 46 , 47 ], seeking significant improvements to reduce the cost of goods and to achieve economical viability. In this study, the production process supported cell growth of HEK293 cells to a density over 4.5 × 10 6 cells/mL during the virus production phase, in which high levels of volumetric and specific cell production yields were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that no hemagglutination inhibition titers were detected in the chickens fully protected by vaccination. This protection could have been mediated by antibodies produced against the F protein that neutralize the virus by binding and preventing attachment to the host cells [ 43 , 54 , 55 ]. This reinforces a key role of the F antigen in its ability to induce a sufficiently potent response against NDV.…”
Section: Discussionmentioning
confidence: 99%